Sintesis Komposit Karbon Aktif TKKSTiO2 dengan Aktivasi Gelombang Mikro untuk Pemurnian Emisi Gas Buang Kendaraan Bermotor - Aqni, Wahyu Nur; Nurhanisa, Mega; Dwiria Wahyuni (Jurnal Ilmu Fisika, 2025)
The palm oil plantation industry generates waste besides palm oil products, including empty palm bunch (EPB). This research examines the emission reduction capabilities of motor vehicle exhaust gases using a composite of activated carbon from EPB-AC/TiO2. Surface morphology characterization of the composite is conducted using Brunauer-Emmett-Teller (BET) and Scanning Electron Microscope (SEM). EPB-AC exhibits an average reduction effectiveness of HC gas based on particle size (50, 100, 150, 200 mesh) sequentially at 34.49%, 37.43%, 39.98%, and 43.56%. The average effectiveness of EPB-AC in reducing CO gas sequentially is 70.29%, 71.30%, 72.86%, and 74%. For CO2 gas, EPB-AC has an average reduction sequentially at 52.6%, 54.25%, 56.52%, and 58.54%. On the other hand, the EPB-AC/TiO2 composite exhibits an average reduction effectiveness of HC gas based on particle size sequentially at 42.38%, 43.42%, 45.1%, and 46.57%. The average effectiveness of the EPB-AC/TiO2 composite in reducing CO gas sequentially is 71.24%, 73.52%, 75.54%, and 76.9%. For CO2 gas, the EPB-AC/TiO2 composite has an average reduction sequentially at 54.93%, 54.25%, 59.76%, and 63.05%. Therefore, the best reduction results occur at a particle size of 200 mesh.